ASUHAN KEBIDANAN PADA IBU BERSALIN NY P DENGAN PEMBERIAN KELAPA UNTUK MENINGKATKAN TENAGA PERSALINAN DI PUSKESMAS TANJUNG BALAI KARIMUN : ASUHAN KEBIDANAN PADA IBU BERSALIN NY P DENGAN PEMBERIAN KELAPA UNTUK MENINGKATKAN TENAGA PERSALINAN DI PUSKESMAS TANJUNG BALAI KARIMUN - Menda, Maria; Franshisca Sihombing, Sarmauli; Juni Ekasari, Dian (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2024)
Childbirth is influenced by three main elements, namely energy (his power of straining), the condition of the birth canal, and the size of the fetus. Foods and drinks that are scientifically proven to be used to facilitate labor are dates, young coconut water, honey and soy milk. Objective To provide comprehensive and continuous midwifery care for mothers giving birth, with management of midwifery care in accordance with midwifery service standards. The midwifery care that is applied is Midwifery Care for Mrs. P. Giving Birth Coconuts to Increase Labor Force. The practice report preparation method is descriptive research using the case study method. The research was conducted at the Tanjung Balai Karimun Health Center in March 2023. The subject used in this case study with midwifery care management was Mrs. P. Results and Conclusions Evaluation of the care provided related to the implementation Midwifery Care for Maternity Mrs. P By Giving Coconuts to Increase Labor Force, there is an Increase in Labor Force for Mothers